2004
DOI: 10.1111/j.1399-3038.2004.00164.x
|View full text |Cite
|
Sign up to set email alerts
|

The relation between obesity and asthmatic airway inflammation

Abstract: Epidemiologic studies suggest increased asthma prevalence in obese subjects. However, the relation between obesity and airway inflammation remains unclear. This cross‐sectional study aims to investigate the relation between obesity indices and exhaled nitric oxide (ENO) and leukotriene B4 (LTB4) in children with asthma. Asthmatic patients aged 7–18 yr old were recruited. Weight‐for‐height Z score was calculated from anthropometry. ENO was measured by online single‐breath method using a chemiluminescence analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
1
6

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 35 publications
4
47
1
6
Order By: Relevance
“…It is particularly interesting that obesity increases the TNFα seric concentration, which when connecting to the receptors placed in the straight muscles of the airways, promotes bronchoconstriction. In addition to these factors, there are others which when altering their concentrations may affect the airways function leading to their hyper responsiveness, which include: leptin, adiponectin and PAI-1 (18,29,30) . It is believed that in obese individuals an association between these hypotheses possibly occurs, which predisposes them to more remarkable EIB triggering.…”
Section: Discussionmentioning
confidence: 99%
“…It is particularly interesting that obesity increases the TNFα seric concentration, which when connecting to the receptors placed in the straight muscles of the airways, promotes bronchoconstriction. In addition to these factors, there are others which when altering their concentrations may affect the airways function leading to their hyper responsiveness, which include: leptin, adiponectin and PAI-1 (18,29,30) . It is believed that in obese individuals an association between these hypotheses possibly occurs, which predisposes them to more remarkable EIB triggering.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is little evidence from population studies that obesity is associated with objective markers of asthma such as airway hyperresponsiveness (AHR), [3][4][5][6][7] airway obstruction 8 or airway inflammation. 9 Asthma is defined by both episodic symptoms and variable airway obstruction. AHR, defined as excessive airway narrowing in response to provoking stimuli, is a marker of the tendency to variable airway obstruction and is a fundamental characteristic of asthma.…”
Section: Introductionmentioning
confidence: 99%
“…112,113 Obese asthmatic children did not have elevated airway LTB 4 . 134 Recent adult studies suggest that obesity may enhance neutrophilic airway inflammation 139 and systemic leukotriene production, 140 though this has not been evaluated in children. Since inhaled steroids are generally ineffective against neutrophilic inflammation, the discovery of neutrophilic inflammation in obese asthmatics is consistent with findings of reduced corticosteroids efficacy in the obese.…”
Section: Airway Inflammationmentioning
confidence: 99%
“…Exhaled nitric oxide levels (a surrogate of eosinophilic inflammation) among obese asthmatic children may be the same or even reduced compared to similar leans. [134][135][136][137][138] A few studies in adult obese asthmatics have shown reduced eosinophilic inflammation compared with similar leans. 112,113 Obese asthmatic children did not have elevated airway LTB 4 .…”
Section: Airway Inflammationmentioning
confidence: 99%